PENEGAKAN HUKUM TERHADAP PELAKU PEMBUAT ALAT PEMBATAS KECEPATAN YANG TIDAK SESUAI DENGAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI KECAMATAN KANDIS - Sopiandi Pakpahan; Zulfikar Jayakusuma; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The increase in the number of traffic accidents from year to year showsthat there is a lack of public awareness about the culture of orderly driving.. Oneof the traffic infrastructure that often causes traffic accidents is the speed limitingdevice or the name of the road embankment or road safety embankment. Theprovisions for the installation of “speed limiting devices” on public roads arealready listed in Article 25 paragraph 1 Letter e Law Number 22 Year 2009. Thepurpose of writing this thesis, namely: First, to determine law enforcementagainst the perpetrators of making speed limiting devices that are not inaccordance with the Law on Traffic and Road Transportation. Second, to find outthe constraints of law enforcement against the perpetrators of makinginappropriate speed limiting devices. Third, to find out the efforts against theperpetrators of making inappropriate speed limiting devices. This type of research can be classified in this type of sociological juridicalresearch, because this research author directly conduct research on the locationsor places studied in order to give a complete and clear picture of the issuesexamined. This research was conducted at the Kandis District, whereas thesample population is a whole party with regard to the issues examined in thisstudy, the data source used, primary data, secondary data and data tertiary,technical data collectors in this study with interviews and literature study.From the results of research and discussion it can be concluded that,First, law enforcement against perpetrators of speed limiting devices that are notin accordance with Law Number 22 of 2009 in Kandis District, Siak Regency stillnot seriously done. Second, constraints in law enforcement due to a lack ofcounseling from the police, lack of cooperation between related parties, and nocomplaints from the public. Third, efforts made by law enforcers includecoordinating with related parties, checking the shop, after which the speed limiteris dismantled, and conducting counseling. prosecutors, conducting training andeducation on diversion and seeking good cooperation between institutions.Keywords: Law Enforcement – Speed Bump - Traffic